Pembandingan Perancangan Bangunan Tahan Gempa Menggunakan SNI 1726:2012 Dan SNI 1726:2019 - Azis Wicaksana; Anis Rosyidah (Jurnal Ilmiah Rekayasa Sipil, 2021)
Indonesia has a code for designing a seismic-resistant building, which has always improved year after year. Start from Peraturan Perencanaan Tahan Gempa Indonesia Untuk Gedung (PPTI-UG) 1983, SNI 1726:2002, SNI 1726:2012, and the latest one is SNI 1726:2019. SNI 1726:2019 experienced some renewal on designing a seismic-resistant building. This research aims to compare spectrum response design and the structural behavior between seismic-resistant building design using SNI 1726:2012 and SNI 1726:2019. The reviewed structure behaviors are base shear force (V), drift (δmax), and story drift (Δ). The study compares the detail of the structural components as well as using SNI 2847:2013 and SNI 2847:2019. The research uses a 10-story building modeling that serves as an apartment building and located in the city of Banda Aceh. Seismic analysis using a spectrum response analysis with Special Moment Resisting Frame (SMRF) structure. The result showed that the peak acceleration (Sa) for the class sites of Medium Land (SD) and Hard Land (SC) were 11% and 26%, respectively, while for Soft Land (SE), there was no increase. The shear force in SNI 1726: 2019 has increased by 19.75% for the X direction and 19.97% for the Y direction. The increase in the shear force is directly proportional to the increase in drift and story drift. In the beam detailing and beam-column connection, there were no significant changes. While in the column detailing, there are additional provisions that cause the transverse reinforcement to be tighter.